Experiencias de la caja de ahorro y crédito solidaria “Mushuk Sisa” de la comunidad San Pablo - Quilo Otavalo, Néstor Raúl (2013)
In the context of local development analyzes the experience of the Savings Credit Union Solidarity "Mushuk Sisa" of the community of San Pablo Canton Urco Cayambe, where it is found that the Solidarity Fund is an alternative local development, and ventures to generate individual and collective, while strengthening organizational and distributes wealth, economic, social and cultural. And we identified barriers and socio- organizational achievements, cultural, economic and administrative. In this context it is identified following achievements: seed capital growth from 1390 to 48667.97, the growth of loans and the outstanding amount of loans of the Savings Credit Union Solidarity "Mushuk Sisa", delivering a total credit 1,205 beneficiaries during the 10 years, 95 % of women agree that it must maintain and strengthen cultural elements has made legal legalization Box Credit Union Solidarity Mushuk Sisa.